Orthopaedic surgery in persons with haemophilia - Rodriguez-Merchan, E. C. (Thrombosis and Haemostasis, 2003)
The orthopaedic problems of haemophilia and the surgical techniques most frequently performed by orthopaedic surgeons on haemophilia patients are summarised in this review article. Sometimes it can be recommendable to carry out two or three orthopaedic surgical procedures in a single operative session, with the aim of solving the functional problem in a more global way, which usually is polyarticular. There is no doubt that such an undertaking implies a greater anaesthetic risk, but also avoids the repetition of surgical procedures and saves factor comsumption. Close cooperation between haematologists, orthopaedic surgeons, rehabilitation physicians, paediatricians, psychologists, physiotherapists and nurses is paramount for the satisfactory result of any orthopaedic surgical procedure. There is no doubt that continuous prophylactic clotting factor replacement (prophylactic therapy) is the optimal way to avoid the orthopaedic problems of haemophilia that can still be seen today. Until such a goal can be reached, the orthopaedic surgeon will continue performing arthrocentheses, synoviortheses, synovectomies, tendon lengthenings, débridements, osteotomies, joint replacements, osteosynthesis of fractures and other less frequent surgical procedures on persons with haemophilia.
Keywords: Haemophilia; orthopaedic surgery; orthopaedic procedures